x^2-2x-15=0
(x-5)(x+3)=0
x=5 x= -3
2007-10-08 06:51:56
·
answer #1
·
answered by mrr86 5
·
1⤊
0⤋
Okay so you are given x^2 - 2x = 15
Subtract 15 from both sides and you have
x^2 - 2x - 15 = 0
So now factor.
x is multiplied by x to get x^2. So far, you have
(x )(x )
Now you need to ask how you get -2 using a negative number and a positive number that also multiply to get 15.
You can get -2 by doing -5 + 3. -5 * 3 gives you 15 as well.
So you have
(x - 5)(x+3)=0
The first solution is
x= 5
and the second is
x = -3
2007-10-08 07:10:37
·
answer #2
·
answered by Teah 1
·
0⤊
0⤋
X(squared) - 2x = 15
=> X(squared) - 2x - 15 = 0
=> (x - 5 )( x+ 3) = 0
=>x = 5 OR x = -3
2007-10-08 06:52:48
·
answer #3
·
answered by harry m 6
·
0⤊
0⤋
x^2 - 2x - 15 = 0
x^2 - 2x + 1 - 1 - 15 = 0
(x - 1)^2 - 16 = 0
(x - 1)^4 - 4^2 = 0
(x - 1 - 4)(x - 1 + 4) = 0
(x - 5)(x + 3) = 0
x1 = 5
x2 = -3
2007-10-08 06:57:14
·
answer #4
·
answered by Amit Y 5
·
0⤊
0⤋
x=5. 5^2 - 2(5) = 15
2007-10-08 06:53:19
·
answer #5
·
answered by mark c 1
·
0⤊
0⤋
This is simple : first balance it out so all the variables and constants are on one side. X^2 - 2x - 15 = 0. Equate to 0.
(X +3)(X-5)
Roots are {-3,5}
2007-10-08 07:04:32
·
answer #6
·
answered by TicToc.... 7
·
0⤊
0⤋
x^2 - 2x = 15
x^2 - 2x - 15 = 0
15 = 3* 5
(3 - 5) = -2
(x - 5) ( x + 3 ) = x^2 + 3x -5x -15 = x^2 - 2x -15 = 0
x^2 - 2x = 15
2007-10-08 07:04:11
·
answer #7
·
answered by Eduardo (lalo) Leal 2
·
0⤊
0⤋
if x square-2x=15
x square-2x-15=0
x square-5x+3x-15=0
x (x-5)+3(x-5)=0
(x-3)(x-5)=0
ans x=3 or x=5
2007-10-08 06:55:26
·
answer #8
·
answered by $jess$ 4
·
0⤊
0⤋
x ² - 2 x - 15 = 0
( x - 5 ) ( x + 3 ) = 0
x = 5 , x = - 3
You make me feel better---I have these days too!
2007-10-11 07:51:16
·
answer #9
·
answered by Como 7
·
0⤊
0⤋
(x-5)(x+3)
2007-10-08 06:56:51
·
answer #10
·
answered by xandyone 5
·
0⤊
0⤋